Exploring group concepts in abstract algebra through ChatGPT: An innovative approach to mathematical teaching and learning - Fadhili Mustafa Mrope (Universitas Sarjanawiyata Tamansiswa, 2024)
Traditional methods often struggle to engage students and effectively communicate the intricacies of abstract algebra. This study aims to explore the future of mathematics teaching, with a focus on integrating group theory concepts into Abstract Algebra using ChatGPT, an advanced language processing AI. Chat transcripts edited with ChatGPT were analyzed to gain insights into the evolving landscape of mathematics education, specifically concerning group theory. Group theory is a fundamental branch of Abstract Algebra poised to shape the future of mathematics instruction. ChatGPT facilitates interactive discussions and problem-solving tasks related to group operations, properties, and theorems, offering personalized explanations and guidance tailored to individual student needs. The study highlights the potential of AI-driven platforms like ChatGPT to revolutionize mathematics education by providing dynamic and engaging learning experiences centered around group theory. Furthermore, the study emphasizes the importance of incorporating group theory into mathematics curricula to foster critical thinking, problem-solving skills, and interdisciplinary connections. Educators are urged to leverage innovative tools like ChatGPT alongside traditional pedagogical approaches to ensure effective teaching and learning. Through thoughtful implementation and ongoing professional development, educators can harness AI's power to create inclusive, equitable, and enriching learning environments, empowering students in abstract mathematical reasoning and analysis.